Christian Theology and Social Welfare: Investigating how Theological Discourses Affect Wealth Distribution and Charitable Practices - Abiodun, Adaramaja Olatayo; Oderinde, Olatundun A (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2025)
Contemporary Christian theology significantly shapes wealth distribution and charitable practices within Nigerian Christian communities. These theological discourses influence attitudes toward wealth, poverty, and the moral obligations of charity. In Nigeria, a notion where poverty and socio-economic inequality persist, churches serve as key actors in social welfare interventions. Despite theological teachings on generosity, socio-economic disparities persist within many church communities. This paper investigates how theological teachings on prosperity, stewardship, and justice shape wealth distribution and charitable practices within Nigerian Christian contexts. The study explores how doctrinal positions translate into practical actions of giving, resource mobilisation, and welfare outreach. Employing qualitative methodology, the study utilises analytical, critical, and expository methods of data interpretation. Preliminary findings reveal that prosperity-oriented theological discourses often encourage individualised giving linked to anticipated divine reciprocity, while churches with a theology of social justice prioritise collective responsibility and structured welfare initiatives addressing systemic poverty. Additionally, eschatological perspectives significantly influence welfare priorities, with some churches emphasising immediate socio-economic transformation while others interpret welfare as spiritual preparation for eternal rewards. This study argues that theology is not a passive endeavour but an active force in shaping socio-economic practices within faith communities, influencing the sustainability, and coordination of charitable activities. By demonstrating the interplay between theological conviction and socio-economic action, the paper contributes to scholarship in practical theology, Christian ethics, and development studies, offering insights into the potential of faith-based organisations as partners in addressing poverty and inequality in Nigeria. Also, the study shows how religious beliefs drive fair wealth sharing and lasting charity within complex societies.